Assembly meshing of abrasive waterjet nozzle erosion simulation - Naqib Hakim, Kamarudin; Mebrahitom, A.; Azmir, Azhari (IOP Publishing, 2017)
Computational Fluid Dynamics (CFD) softwares have been prevalent in Abrasive Waterjet (AWJ) Modelling for optimization and prediction. However, there are many different methods in approaching a single problem especially in predicting the erosion rate of nozzle which is critical in influencing kerf quality of AWJ cutting. In this paper, three main methods of assembly meshing for an abrasive waterjet erosion were simulated which is Quadrilateral,Cutcell and Tetrahedrons and each processing time, quality of convergence and accuracy of results are discussed. Results shows that Quadrilateral mesh prevails in the mentioned category followed by Tetrahedrons and Cutcell.